Noise from online discussion forums: Evidence from IPOs in China - Qingqing Fei (China Journal of Accounting Research, 2021)
In this study, we use initial public offerings (IPOs) in China to investigate how online stock forums influence information asymmetry and IPO valuation. The empirical analysis isolates the underpricing and overvaluation components of initial returns. The number of forum comments, postings, and readings are positively associated with initial returns and the degree of underpricing, implying that forums create noise that exacerbates information asymmetry during IPOs. This effect is amplified by the quiet period regulation, which drives investors to rely on online discussion forums to obtain information. Through sentiment analyses of forum posts and media coverage, we find that the negative effect of online forums is more prominent when bad news prevails. We clarify the role of online stock forums in IPO pricing and information asymmetry by separating underpricing from overvaluation in initial returns.
Keywords: 650; Online forum; IPO valuation; Underpricing; Overpricing; Quiet period; Online posting